Relevance of English in Today’s world: The Changing Role of English Language in the Modern World (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The new millennium brought new challenges and newavenues in every field. We have a changed scenario as a result ofglobalization, liberalization and scientific document. A new thought processand ideas diffused in the environment English become the Lingual France of theworld. At the same time certain subjects holding an important position in thepast lost their same status.